Hierarchical looping results in extreme extensibility of silk fibre composites produced by Southern house spiders (Kukulcania hibernalis) - Liprandi, Daniele (2024)
Spider silk is a tough and versatile biological material combining high tensile strength and extensibility through nanocomposite structure and its nonlinear elastic behaviour. Notably, spiders rarely use single silk fibres in isolation, but instead process them into more complex composites, such as silk fibre bundles, sheets and anchorages, involving a combination of spinneret, leg and body movements. While the material properties of single silk fibres have been extensively studied, the mechanical properties of silk composites and meta-structures are poorly understood and exhibit a hereto largely untapped potential for the bio-inspired design of novel fabrics with outstanding mechanical properties. In this study, we report on the tensile mechanics of the adhesive capture threads of the Southern house spider (Kukulcania hibernalis), which exhibit extreme extensibility, surpassing that of the viscid capture threads of orb weavers by up to tenfold. By combining high-resolution mechanical testing, microscopy and in silico experiments based on a hierarchical modified version of the Fibre Bundle Model, we demonstrate that extreme extensibility is based on a hierarchical loopson- loops structure combining linear and coiled elements. The stepwise unravelling of the loops leads to the repeated fracture of the connected linear fibres, delaying terminal failure and enhancing energy absorption. This principle could be used to achieve tailored fabrics and materials that are able to sustain high deformation without failure.